2006
DOI: 10.1136/ard.2005.041186
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoma and other malignancies in primary Sjogren's syndrome: a cohort study on cancer incidence and lymphoma predictors

Abstract: A 16-fold increased risk for development of NHL was found. CD4+ T lymphocytopenia is an additional strong risk factor for developing lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
404
4
32

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 502 publications
(456 citation statements)
references
References 41 publications
16
404
4
32
Order By: Relevance
“…A retrospective study of Swedish patients with "non-AECC" sicca syndrome did not observe an increased risk of cancer (standardized incidence ratio [95% confidence interval]: 0.77 [0.41-1.32]). Interestingly, neither acute leukaemia nor lymphoma was diagnosed [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study of Swedish patients with "non-AECC" sicca syndrome did not observe an increased risk of cancer (standardized incidence ratio [95% confidence interval]: 0.77 [0.41-1.32]). Interestingly, neither acute leukaemia nor lymphoma was diagnosed [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have focused on the risk of neoplasia in SS [10][11][12][13][14], we found only four publications in which acute leukaemia was cited ( Table 1) [15][16][17][18]. The first publication reported on a 59-year-old woman with primary SS diagnosed in 1963.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The patients are also at higher risk of developing lymphoma, a well-identified cause of mortality in pSS. [Ramos-Casals et al 2005;Theander et al 2004Theander et al , 2006.…”
Section: Treatment Of Other Glandular Manifestationsmentioning
confidence: 99%
“…The systemic nonexocrine manifestations may include constitutional symptoms (fatigue, arthralgia, myalgia and low-grade fever), arthritis, skin lesions, leukocytoclastic vasculitis, Raynaud's phenomenon, central and peripheral neurologic involvement, renal, lung or hepatic involvement and finally lymphoproliferative disorders [Ramos-Casals et al 2005]. The presence of vasculitis, cryoglobulinaemia and low complement levels characterizes a subset of patient with higher morbidity and mortality mainly related to the higher probability to develop lymphoma [Ramos-Casals et al 2005;Theander et al 2004Theander et al , 2006. SS may occur as a primary disorder (pSS) or in association with other systemic autoimmune diseases, traditionally defined as secondary SS (sSS), such as rheumatoid arthritis, and systemic lupus erythematosus [Ramos-Casals et al 2007].…”
mentioning
confidence: 99%
See 1 more Smart Citation